2000
DOI: 10.1006/jabr.2000.8396
|View full text |Cite
|
Sign up to set email alerts
|

Uniformity of the Meager Ideal and Maximal Cofinitary Groups

Abstract: We prove that every maximal cofinitary group has size at least the cardinality of the smallest non-meager set of reals. We also provide a consistency result saying that the spectrum of possible cardinalities of maximal cofinitary groups may be quite arbitrary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 8 publications
1
30
0
Order By: Relevance
“…A systematic study of mad permutation families was suggested by S. Thomas (see [14]) and many results have been obtained (see, e.g. [3,7,14,17], etc.). As to the relationship between maximal cofinitary permutation groups and mad permutation families in Sym(N), some preliminary study on set theoretic aspects of the two has been done in [15,19].…”
Section: Open Problem 12 Does There Exist a Concrete Example Of Maxmentioning
confidence: 97%
See 1 more Smart Citation
“…A systematic study of mad permutation families was suggested by S. Thomas (see [14]) and many results have been obtained (see, e.g. [3,7,14,17], etc.). As to the relationship between maximal cofinitary permutation groups and mad permutation families in Sym(N), some preliminary study on set theoretic aspects of the two has been done in [15,19].…”
Section: Open Problem 12 Does There Exist a Concrete Example Of Maxmentioning
confidence: 97%
“…A group G Sym(N) is cofinitary or sharp if g is cofinitary for all g ∈ G \ {id}. For a discussion of different aspects of cofinitary groups, our reader can consult the well-written survey paper [4] by P. Cameron. Various research has been done concerning the structure of maximal cofinitary groups (see, e.g., [1][2][3]6,12,13,16,17], etc.). Most of the research has been focused on combinatorial properties and cardinalities of maximal cofinitary groups.…”
Section: Introductionmentioning
confidence: 99%
“…We want to enlarge this group by σ * ∈ S ∞ , such that all of G, σ * is cofinitary. This can be done using a forcing invented by Zhang [22], which has proven extremely valuable in applications (see [2,23,8,24,14,7,13]). …”
Section: Coding Into a Generic Group Extensionmentioning
confidence: 99%
“…the least size of a mcg, to other cardinal invariants of the continuum; see e.g. [22,23,8,2,6]. Analogous questions about permutation groups on κ, where κ is an uncountable cardinal, have also been studied; see e.g.…”
Section: Introduction (A)mentioning
confidence: 99%
“…We will then show that we can, in fact, get a suitably "wide" slalom which is eventually disjoint from all slaloms in F (Lemma 2.6). Lemma 2.4 was independently discovered and used by Brendle, Spinas and Zhang [5].…”
Section: A Van Douwen Mad Family In Zfcmentioning
confidence: 99%